A critical appraisal of the clinical effectiveness of a fixed combination of valsartan, amlodipine, and hydrochlorothiazide in achieving blood pressure goals - Cheryl L Laffer; Fernando Elijovich (Dove Medical Press, 2011)
Cheryl L Laffer1, Fernando Elijovich21Section of Hypertension and Vascular Medicine, 2Division of General Internal Medicine, Department of Medicine, Texas A&M Health Sciences Center College of Medicine, Temple, TX USAAbstract: Recent guidelines for the treatment of hypertension have focused on the need for multiple medications to get most patients to goal blood pressure (BP). Two to three different classes of antihypertensive agents are frequently required, increasing the risk of poor compliance with therapy. Hence, the guidelines have recommended starting with combination therapy in patients with BP that is over 20 mm Hg systolic or 10 mm Hg diastolic above goal. The latest advance in treatment regimen has been the development of triple-therapy combinations of an angiotensin receptor blocker, amlodipine, and hydrochlorothiazide. We review the pathophysiologic rationale for such a combination and the efficacy, safety, and tolerability of the first triple therapy that has become available: valsartan + amlodipine + hydrochlorothiazide. Finally, we suggest that use of triple therapy could improve the accuracy of diagnosing resistant hypertension, an increasingly prevalent and severe condition, by enhancing adherence to treatment and weeding out patients with pseudoresistance. This would allow for implementation of expensive and invasive workup only in those truly resistant patients in whom it is justified.Keywords: combination therapy, compliance, hypertension control rates, resistant hypertension